2024
DOI: 10.1039/d3na00579h
|View full text |Cite
|
Sign up to set email alerts
|

Carbon sphere doped CdS quantum dots served as a dye degrader and their bactericidal behavior analysed with in silico molecular docking analysis

Muhammad Ikram,
Misbah Naz,
Ali Haider
et al.

Abstract: We have employed a co-precipitation method to synthesize different concentrations of carbon spheres (CS) doped with cadmium sulfide (CdS) quantum dots (QDs) for catalytic reduction and antibacterial applications. Various morphological...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…The efficiency of the removal of TOC could be calculated by (1 − TOC TOC 0 ) × 100%, where TOC represents the instantaneous saturation of total organic carbon and TOC 0 represents the initial saturation of total organic carbon. An analysis of Figure S8b revealed that following 152 min of VLE, the REF values of TOC within pesticide wastewater were 97.19%, 83.33%, 77.81%, and 28.68% when employing HBHP, Ho 2 YSbO 7 , Bi 2 MoO 6 , and NTO as photocatalysts, respectively, for the treatment of DRN [97,98]. Moreover, a comparison of the TOC mineralization effectiveness after 152 min of VLE revealed the superior performance of HBHP, surpassing that of Ho 2 YSbO 7 by 1.17 times, Bi 2 MoO 6 by 1.25 times, and NTO by 3.39 times.…”
Section: Photocatalytic Activity Photocatalytic Activity In Photodegr...mentioning
confidence: 99%
“…The efficiency of the removal of TOC could be calculated by (1 − TOC TOC 0 ) × 100%, where TOC represents the instantaneous saturation of total organic carbon and TOC 0 represents the initial saturation of total organic carbon. An analysis of Figure S8b revealed that following 152 min of VLE, the REF values of TOC within pesticide wastewater were 97.19%, 83.33%, 77.81%, and 28.68% when employing HBHP, Ho 2 YSbO 7 , Bi 2 MoO 6 , and NTO as photocatalysts, respectively, for the treatment of DRN [97,98]. Moreover, a comparison of the TOC mineralization effectiveness after 152 min of VLE revealed the superior performance of HBHP, surpassing that of Ho 2 YSbO 7 by 1.17 times, Bi 2 MoO 6 by 1.25 times, and NTO by 3.39 times.…”
Section: Photocatalytic Activity Photocatalytic Activity In Photodegr...mentioning
confidence: 99%